RESPON NELAYAN TERHADAP PROGRAM BANTUAN PEMERINTAH DESA TANJUNG LUMBA-LUMBA KECAMATAN KUBU KABUPATEN ROKAN HILIR - Sri Wahyuni; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The purpose of this research is to analyze fishermans'response about funding programm from government and the influencing factors of the funding programm in Desa Tanjung Lumba-lumba Kecamatan Kubu Kabupaten Rokan Hilir. Population o this research is people work as fisherman. There are 30 fishermans in Desa Tanjung Lumba-lumba Kecamatan Kubu Kabupaten Rokan Hilir. 15 of them receive government's funding. All population member become sample. Data is analyzed descriptive quantitatively. Result shows that factors influence respondents who do not receive the fund are: low level education, lack of knowledge, and fishermans' age. There are 12 respondents (40%) do not know about the fund, 18 respondents (60%) know about it. The most dominant factor is lack of knowledge and mostly of them already have a home.Keyword: response, fisherman,government's funding programm.